2017
DOI: 10.1186/s12879-017-2500-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic findings as a determinant and no effect of macrolide resistance on clinical course of Mycoplasma pneumoniae pneumonia

Abstract: BackgroundWith the emergence of macrolide resistance, concerns about the efficacy of macrolides for the treatment of Mycoplasma pneumoniae (MP) pneumonia in children have been raised. This study aimed to determine the effect of macrolide resistance on the outcome of children who were hospitalized with MP pneumonia.MethodsBetween 2010 and 2015, we performed culture of MP from nasopharyngeal samples obtained from children who were hospitalized with pneumonia at five hospitals in Korea. Macrolide resistance was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 33 publications
6
50
0
Order By: Relevance
“…Macrolides are still used as rst-line agents at high frequencies in countries with a high burden of MR-MP strains, such as China and Japan, mainly because of their low minimum inhibitory concentrations against the MP, anti-in ammatory effect and low toxicity in children. Yoon et al reported macrolide treatment for macrolidesusceptible MP pneumonia did not contribute to signi cant clinical improvement compared to no antimicrobial treatment [13] . Yang et al reported corticosteroid therapy might prevent disease progression, and anti-MPantibiotics may have limited effects on MPP [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Macrolides are still used as rst-line agents at high frequencies in countries with a high burden of MR-MP strains, such as China and Japan, mainly because of their low minimum inhibitory concentrations against the MP, anti-in ammatory effect and low toxicity in children. Yoon et al reported macrolide treatment for macrolidesusceptible MP pneumonia did not contribute to signi cant clinical improvement compared to no antimicrobial treatment [13] . Yang et al reported corticosteroid therapy might prevent disease progression, and anti-MPantibiotics may have limited effects on MPP [1] .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that SMPP is the most strongly associated risk factor for MPassociated thrombosis. The severity of MPP was associated with fever duration, the levels of inflammatory markers such as CRP and LDH, and the severity of radiography findings such as lobar consolidation [21][22][23][24] , which are strongly correlated with measures of the severity of airway damage such as mucous necrosis and subsequent airway remodeling [4] . The present study again confirmed the above associations, and the presence of an excessive systemic and local airway immune response in SMPP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the MRMP group, the duration of fever, cough, hospitalization was longer and the rate of change to alternative antibiotics was higher than the MSMP group ( 20 21 ). However, a recent study reported that macrolide resistance alone has no effect on clinical course of M. pneumoniae pneumonia ( 22 ). In our study, the contribution of macrolide resistance on clinical course was not found like the latter report.…”
Section: Discussionmentioning
confidence: 99%